Developing a program for pediatric urological care in the community - Papanikolaou, Frank; Lee, Linda (Canadian Urological Association Journal, 2017)
The growth of large metropolitan areas across Canada has fostered the need to provide tertiary care to patients outside of the traditional university-affiliated hospitals. Subspecialty urology care at centres of excellence in the community includes urological oncology, men’s health, community urology, and pediatric urology. The two of us have developed such centres of excellence in pediatric urology in the community settings of Mississauga, ON, and Victoria, BC. This article highlights personal experiences in developing these programs and the lessons learned. It is hoped that this can help guide similar undertakings by others to develop centres of excellence in subspecialty urology care so as to bring care closer to patients’ homes.